Disseminated echinococcosis with lung, hepatic, pancreatic and splenic involvement: A case report - Azañero-Haro, Johan (2023)
Hydatidosis is a parasitic zoonosis caused by Echinococcus, with rural livestock areas the most prevalent. It constitutes a public health problem, with Peru being one of the most affected countries. The granulosus genus is responsible for cystic disease, predominantly affecting the liver and lungs. Disseminated hydatidosis is the simultaneous involvement of multiple organs and, as rare, is a diagnostic challenge. We present the case of a man with disseminated hydatidosis complicated by the rupture of one of the lung cysts, which had been incidentally diagnosed by imaging studies. Due to pulmonary, hepatic, pancreatic and splenic involvement, he received albendazole for 9 uninterrupted months with the disappearance of most of the lesions at the lung, hepatic and splenic levels. Currently, the management of disseminated hydatidosis there is no consensus, although surgery, percutaneous drainage and medical treatment remain fundamental pillars for hydatidosis. The interest of this publication is the management and follow-up of medical treatment of this rare presentation of disseminated hydatidosis.